Analisis Kebijakan Pemerintah Daerah dalam Pengelolaan Keuangan dan Alokasi Dana Desa - Safira Mukaromah; Nashva Azzahra Maharani Safitri; Lukas Imanuel; Marcelleno Marcelleno (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
This study aims to explore the local government's policies on financial management and the allocation of village funds. These policies are designed to expedite and enhance the effectiveness of development programs as well as promote equitable development throughout Indonesia, which was previously primarily regulated by the central government. By granting greater authority to local governments, it is expected that development policies can be more adaptive and responsive to the needs of rural communities in their respective regions. The concept of local government financial management encompasses fundamental principles that should be followed, including transparency, accountability, effectiveness, and efficiency. Transparency refers to the acquisition of information during budget preparation and implementation, as well as the publication of relevant financial information. Effectiveness and efficiency are related to the local government's ability to manage public finances while considering objectives and available resources. The effectiveness of local government's financial management in handling village funds is the result of various interconnected factors, such as the presence of good policies and governance in fund management. The role of communities in supervising the utilization of village funds should not be disregarded. Through mechanisms such as village deliberations, information technology utilization, and the establishment of village oversight institutions, communities can monitor and supervise the use of village funds more effectively. The local government's policies on financial management and the allocation of village funds play a crucial role in accelerating rural development. Targeted allocation of village funds, along with effective and efficient financial management, can enhance the well-being of rural communities and help reduce social tensions between urban and rural areas.